التسوق الالكتروني ودوره في نشر ثقافة الاستهلاك: دراسة وصفية مطبقة في مدينة المنيا - كشك، حنان محمد عاطف (جامعة قناة السويس - كلية الآداب والعلوم الإنسانية, 2019)
The main object of the present study is to focus on the role of E-shopping as one of the modern mechanism used by the world companies to overcome the markets and consumers, as well as multi media that spreading the culture of consumption, and providing the individuals with consumed goods and items, and services that they may not be in need of, or they may not be matching with their needs, their living levels, or even it is not matching with the priorities of the society. It is an effort to reach to some suggestions that will limit spreading the phenomenon of recreational consumption in the society. The theoretical approach was based on two models: the Thorsten Veblen model of the luxury class, and the Pierre Bourdieu model on consumption, Capital and class differentiation. The study belongs to the pattern of descriptive studies; therefore, they used the methodology of social survey based on the sample It is ONE OF the' most suitable methodologies matching with the descriptive studies. The study depended on the questionnaire as a main tool for all the data via applying on a sample of marketers through the internet, consists of (238) customers. The most fundamental findings that the study reached was that, the increase of spreading of modern consumption culture has lead to changing the patterns and methods of consumption, as the increase' in spreading great amount in travelling, recreation, obtaining the most recent of modern mobiles, regardless the need for it, also spreading lavishly on social and family events. The sample of the survey according to the findings of the study showed that they prefer the foreign goods, and seek the well-known brands. It has been shown that the large number of advertising through the websites and the internet pay the vast majority of the sample to buy goods they do not need, and may not use them in their daily lives. The proliferation of advertising has transformed some goods, which will recently were considered to be luxury goods, where the vast majority of the sample of the study assured that the internet has increased their consumption of large quantities of luxury goods It was found that the most inclined to the emotional link to goods and buy more goods that do not need it , and to be keen to acquire international brands, and affected by the large number or advertisement are female ,youth and the sample members who have additional income. The findings have shown that the internet has its main role played in increasing the consumption. The more the period of using the internet, the more the number of purchasing, and the more it falls under the influence of adverting and delusion cuts and the more linked to the goods. Recommendation: The study recommended that cultural sessions conducted by the socialists .religious people must be held for spreading the consumption awareness, and the awareness of the importance of rationalizing of spending to limit the culture of consumption that has been spreading in the Egyptian society.
يتمثل الهدف الرئيس للدراسة الراهنة في محاولة الوقوف على دور التسوق الإلكتروني كأحد الآليات الحديثة التي تستخدم من قبل الشركات العالمية للهيمنة على الأسواق والمستهلكين وما يقدمه من وسائل إعلانية متعددة في نشر ثقافة الاستهلاك وتحفيز الأفراد على استهلاك سلع وخدمات قد لا يكونوا في حاجة إليها، أو قد لا تتفق مع احتياجاتهم وأوضاعهم المعيشية بل ولا تتفق وأولويات المجتمع، وذلك كمحاولة للوصول إلى بعض المقترحات التي تعمل على الحد من تفشي ظاهرة الاستهلاك الترفي في المجتمع، وقد اعتمدت الدراسة في توجهها النظري على نموذجين نظريين وهما نموذج "ثورشتاين فيبلين" عن الطبقة المترفة ونموذج "بيير بورديو" عن الاستهلاك ورأس المال والتمايز الطبقي. وتنتمي الدراسة إلى نمط الدراسات الوصفية ولذا تم الاعتماد على منهج المسح الاجتماعي بالعينة لأنه يعد من انسب المناهج ملائمة للدراسات الوصفية، واعتمدت الدراسة على الاستبيان كأداة رئيسة في جمع البيانات من خلال التطبيق على عينة عمدية من المتسوقين عبر الإنترنت بلغ قوامها ٢٣٨ مفردة. ومن أهم النتائج التي توصلت إليها الدراسة أن زيادة انتشار الثقافة الاستهلاكية الحديثة قد أدى إلى إحداث تغيرات في أنماط وأساليب الاستهلاك تمثلت في زيادة أنفاق نسبة كبيرة من أفراد العينة على السفر والترفيه والحرص على اقتناء أحدث أجهز المحمول بغض النظر عن الحاجة إليها، والإنفاق ببذخ في المناسبات الاجتماعية والعائلية والحرص على اقتناء كل ما هو جديد من السلع رغبة منهم في التميز والظهور، وتفضيل السلع الأجنبية والبحث عن السلع ذات الأسماء التجارية الشهيرة كما تبين أن كثرة الدعاية والإعلانات عبر صفحات الإنترنت تدفع الغالبية العظمى من أفراد العينة لشراء سلع ليسوا بحاجة إليها وقد لا يستعملونها في حياتهم اليومية، كما أن كثرة الدعاية والإعلانات قد حولت بعض السلع والتي كانت إلى وقت قريب تعد سلع كمالية إلى سلع ضرورية. حيث أكدت الغالبية العظمي من أفراد عينة الدراسة بأن الإنترنت زاد من استهلاكهم بصورة كبيرة للسلع الكمالية. وتبين أن أكثر الفئات ميلاً إلى الارتباط العاطفي بالسلع وشراء المزيد من السلع التي لا يحتاجوا إليها والحرص على اقتناء الماركات العالمية والتأثر بكثرة الدعاية والإعلانات هم الإناث وفئة الشباب وأفراد العينة الذين يمتلكون دخول إضافية، وأظهرت النتائج بأن الإنترنت له دور رئيس في زيادة الاستهلاك فكلما طالت فترة استخدام الفرد للأنترنت كلما زادت عدد مرات الشراء وكلما وقع تحت تأثير الدعاية الإعلانية والتخفيضات الوهمية وكلما أصبح أكثر ارتباطاً بالسلع، وقد أوصت الدراسة بضرورة عقد ندوات تثقيفية من قبل علماء الاجتماع ورجال الدين لنشر الوعي الاستهلاكي والتوعية بأهمية ترشيد الانفاق للحد من ثقافة الاستهلاك التي تفشت في المجتمع المصري
Keywords: التسوق الإلكترونى -- الثقافة الاستهلاكية -- الدعايا الإلكترونية -- مدينة المنيا -- مصر